Telomerase reverse transcriptase synergizes with calorie restriction to increase health span and extend mouse longevity. - Elsa Vera (Public Library of Science (PLoS), 2013)
Caloric restriction (CR), a reduction of food intake while avoiding malnutrition, can delay the onset of cancer and age-related diseases in several species, including mice. In addition, depending of the genetic background, CR can also increase or decrease mouse longevity. This has highlighted the importance of identifying the molecular pathways that interplay with CR in modulating longevity. Significant lifespan extension in mice has been recently achieved through over-expression of the catalytic subunit of mouse telomerase (mTERT) in a cancer protective background. Given the CR cancer-protective effects in rodents, we set to address here whether CR impacts on telomere length and synergizes with mTERT to extend mouse longevity. CR significantly decreased tumor incidence in TERT transgenic (TgTERT) mice and extended their lifespan compared to wild-type (WT) controls under the same diet, indicating a synergy between TgTERT and CR in increasing mouse longevity. In addition, longitudinal telomere length measurements in peripheral blood leukocytes from individual mice showed that CR resulted in maintenance and/or elongation telomeres in a percentage of WT mice, a situation that mimics telomere dynamics in TgTERT cohorts. These results demonstrate that CR attenuates telomere erosion associated to aging and that synergizes with TERT over-expression in increasing "health span" and extending mouse longevity.